Intelligence isn't enough : a black professional's guide to thriving in the workplace - Anderson, Carice (Berrett-Koehler Publishers, 2022)
Knowing others-building and sustaining important relationships in the workplace " Knowing your environment-analyzing your organization's culture Anderson will teach you how to integrate the knowledge of these three groups to craft an authentic personal brand and communication style that will help you maximize your impact. Using personal stories, quotes, lessons learned, and advice from both the author and Black leaders who have worked in some of the finest institutions across North America, Africa, and Europe, Black professionals will learn tips and tools to strategically chart their career paths and advance in the workplace for lifelong success